FRI0027 Adam17 influences the gro-a/cxcr2 system expression in sjögren's syndrome. (23rd January 2014) - D'amore, M.; Sisto, M.; De Lucro, R.; Ribatti, D.; Lisi, S.
Abstract : Background: Growth related oncogene-alpha (GRO-α), a member of the CXC chemokine family, and its receptor CXC chemokine receptor 2 (CXCR2) are involved in the inflammatory processes. In many models of acute and chronic inflammatory diseases, blockade of CXCR2 substantially reduces leukocyte recruitment, tissue damage and mortality. There are evidences that the CXCR2 expression can also be regulated, by enzymatic cleavage via metalloproteinases. Actually, the ADAM17 inhibitors are under development for the treatment of a variety of inflammatory autoimmune disorders. In addition, the ADAM17 activation was recently associated with the chronic inflammatory condition observed in Sjögren's syndrome (SS). Objectives: To better understand the molecular mechanisms by which the GRO-α /CXCR2 system is involved in the SS inflammatory condition and clarify the role of ADAM17 activation in the modulation of the GRO-α/CXCR2 chemokine system in epithelial cells (SGEC) from SS salivary glands. Methods: RT-PCR, Real Time-PCR, western blot, ELISA, flow cytometry techniques were employed to examine the expression of GRO-α /CXCR2 system in presence or not of the ADAM17 inhibitor TAPI-1 in salivary gland epithelial cells cultures from SS patients. Results: The CXCR2 overexpression observed in SS SGEC resulted dramatically decreased by ADAM17 inhibitor TAPI-1. In addition, comparing the expression levels of ADAM17 in healthy SGEC in presence or not of GRO-α treatment, we observed that GRO-α, dose-dependently, influences ADAM17 activation, effect that was inhibited by blocking the interaction of GRO-α with its CXCR2 receptor. Conclusions: Our data show for the first time that ADAM17 has an important role in GRO-α/CXCR2 system activity regulation, suggesting that regulating CXCR2/ADAM17 interaction could be an attractive therapeutic target in SS. Disclosure of Interest: None Declared